Delinquency in regions under intensified industrialization and the relations between the dynamics of delinquency and the dynamics of socio-economic processes (1958-1960 and 1964-1966) (Archives of Criminology, 1969)
The study consists of two parts. The first part is concerned with the development of delinquency in 4 regions under intensified industrialization programmes, whereas the other part deals with the relationships between the dynamics of socio-economic processes and the dynamics of delinquency, against the background of all the provinces in Poland.The studies discussed in both parts have been based on the police statistics of offences reported on and they embrace two periods: 1958-1960 and, 1964-1966.I. To illustrate a socio-demographical character of the 4 regions under intensified industrialization programmes, in addition to a periodization of the industrialization processes, presented by Professor J. Szczepański, also a scheme of socio-demographic processes in regions under industrialization programmes, prepared by Professor Rajkiewicz, has been taken into account.Stages of industrialization on the regional levels, differentiated by Professor J. Szczepański, are as follows:1. Planning, which includes only those tasks which are considered indispensable for preparing an all-aspect industrialization plan on the particular region's level.2. Construction of new industrial objects and substantial auxiliary premises.3. Initial start of new industrial plants and completion of substantial auxiliary premises.4. Achievement of stabilization and the new balance of conditions.In Piofessor A. Rajkiewicz's scheme of socio-demografic processes in regions under industrialization programmes, the following components have been differentiated (according to their growing intensification): migration processes, occupational activation of unemployed labour, employment mobility (chiefly consisting in frequent changes of places of employment by unskilled labour), achievement and improvement of occupational skill, crew forming in new places of employment.Empirical indices have been determined for such processes and it has been ascertained at the same time, that both intensification and dynamics of migration processes, activation of unemployed labour and employment mobility, generally speaking, achieved greatest intensity in stages of construction of industrial objects and of initial start of new industrial plants (especially in its primitive phase). On the other hand, the processes of achievement and improvement of occupational skills as well as that of the formation of crews in new places of employment were particularly characteristic for the stage of stabilization and new balance of interhuman relations.Problems of migration processes, occupational activation of unemployed labour as well as the problem of employment mobility, are related with the increased horizontal mobility. Since their nature consists either in mass migration or in frequent changes of places of employment by unskilled labour, therefore, those processes lead to the relaxation of environmental ties and to the slackening of social control over the individuals concerned. Thus, such processes may favour the development of certain forms of social disorganization including the intensification of delinquency.The processes of achievęment and improvement of occupational qualifications by those employed in the national economy or the processes of crew forming in new places of employment substantially consist in achieving a mass advance of individuals within a social structure and create conditions capable of developing stabilized communities with a normally functioning social control. Therefore, such processes may be recognized to be one of the social vertical mobility forms which consists in a mass advance of social nature in the population of the region concerned. Such a phenomenon should exercise some inhibitive influence on any signs of social disorganization and, consequently, on a decrease in delinquency. The abovementioned hypotheses have been confirmed by the findings obtained from the investigations of the development of delinquency observed in 4 regions under intensified industrialization programmes.To begin with, the total delinquency rates and dynamics in the regions in question were confronted with those in the provinces concerned. As for 1964-1966, it had been found that delinquency rates in the regions under industrialization programmes were considerably higher than those in the provinces. The total delinquency rate per 10 thousand inhabitants of the regions under industrialization programmes was 131.89 while that of the provinces concerned - 104.10. The biggest difference was found in the offences against social property, the rates having been 34.01 and 20.75, respectively; a significant difference was also found in robberies (1.06 against 0.66), clerical offences, very severe and severe bodily injury and offences against private property.Having confronted the delinquency dynamics between 1958-1960 and 1964-1966, it has been established that in the latter period, the rates of delinquency had considerably increased in the regions under industrialization programmes and showed simultaneous decrease in the provinces concerned. The general delinquency rates in the regions increased by 19.9 percent and those in the provinces decreased by 11.4 per cent. In the regions under industrialization programmes, the highest increase was noted in the robbery rate, namely by 165.0 per cent, against that by 46,7 per cent in the provinces; next came offences against social property (an increase in rate by 55.9 per cent in the regions and a decrease by 12.7 per cent in the provinces), finally, offences against private property (an increase in rate by 16.9 in the regions and a decrease by 16.9 per cent in the province).Of particular importance seems to be a finding from that analysis which concludes that the increase in delinquency in the particular regions of intensified industrialization programmes appears to be closely related with the industrialization stages achieved in those particular regions, on the one hand, and with the intensity or-some of the abovediscussed socio-economic processes, on the other. In 1964-1966, out of the four studied regions under intensified industrialization programmes, the first one reached the stage of construction of industrial objects and substantial auxiliary premises, the second and the third - were in the course of the initial start of new industrial plants and the completion of substantial auxiliary premises, and in the fourth one - stabilization and new balance of conditions was partially achieved. At the same time, in the first three regions, one observed considerable intensity of migration processes, occupational activation of unemployed labour and employment mobility which - as has already been mentioned - were connected with the increased social horizontal mobility. However, in the fourth region, the intensity of such processes was already considerably lower though other processes manifested themselves more clearly, namely the processes of achievement and improvement of occupational skills by those employed in the social economy as well as the process of the formation of crews in new places of employment, i.e., those processes which owing to the nature of the mass social advance are one of the forms of social vertical mobility.In 1958-1960 and 1964-1966, in the first three regions of intensified industrialization, there was an apparent increase in delinquency rates, especially in the latter period, in which the regional rates were considerably higher than the provincial ones. But at the same time in the fourth region, there was an evident decrease in delinquency rates and as for 1964-1966, the rates were even lower than in the province concerned.It may then be assumed that it is only two stages of intensified industrialization which might be recognized as those whięh favour an increase in delinquency rates, namely: the stages of construction of new industrial objects and of the initial start of new plants. The most rapid increase in delinquency rates is observed in the course of a few years after capital investments have been commenced, i.e. in the stage of construction of new industrial objects and in the early stage of the initial start of new industrial plants. It should be expected that higher rates of delinquency in the regions of intensified industrialization have a temporary character only, connected with greater social horizontal mobility and will certainly decline in accordance with the intensification of the processes of social advance of the population concerned.II. In the second part of the study, the relationships between the dynamics of socio-economic processes and that of delinquency have been analysed on the basis of the material collected from all the provinces in Poland. 79 variables were used in the analysis, including 15 concerned with delinquency. The rate was defined as a per-cent increase or decrease in the individual variables values in 1964-1966 against 1958-1960 (the value of the variable for 1958-1960 was 100 per cent). A method by J. Perkal, a Polish mathematician, was used, the so called ,,analysis of a set of characteristic" which is a simplification of L. L. Thurstone's multiplefactor analysis. 18 factors, referred to as processes, were obtained. 6 of these are particularly important for the topic of this study.Before we proceed with the discussion of the findings of that analysis mention must be made of the fact that in Poland, as compared with 1958-1960, a general decrease in the number of offences took place in 1964-1966. This is reflected in the formulations, concerning the relationships between the dynamics of socio-economic processes and that of delinquency, where mostly a slower or quicker decease in the number of offences, connected with the given process, is mentioned and not an increase of the delinquency itself.First of all, let us list three essential processes - from the industrialization and urbanization problems point of view - which in the light of the analysis failed to have shown any significant relation with the delinquency dynamics:1. The rate of the economic development of the provinces (it should be noted, however, that there is a slight dependence between that process and an increase in juvenile delinquency).2. The rate of the industrialization progress in the provinces.3. The rate of the increment of the urban population in the provinces (it should be pointed out that recently in Poland, contrary to many other countries, migration to towns, having to a considerable extent been limited and controlled, essentially consists in a migration of experts wanted for the national economy).Let us mention now three socio-economic processes whose relationships with the delinquency dynamics are apparent:4. A process, clearly marked in certain provinces, characterized by swift increment of the density of population, showing stabilization in a majority of branches of the national economy, (except for an increase in agricultural production), a process which, as compared with other provinces, is connected with a slower decrease in general delinquency, and especially with a decrease in offences against social or private property and in very severe or severe bodily injury. A swift increment of the population number which, except for agriculture, in certain areas was not accompanied by adequately swift economic progress seems to be a factor that might have a disadvantageous effect on the development of delinquency, adding in those areas to a slower decrease in delinquency rates.5. A process, marked in certain provinces only, in which an increase in the proportion of employees of the lowest education level is observed, is connected, as compared with other provinces, with a slower rate of decrease in the total number of offences, especially of those against social or private property, on one hand, and with a quicker rate of increase in offences against public order officers and in certain offences against the person, on the other. It should be noted that that particular process is approximate in character to one which was dealt with in the first part of this study, typical for intensified industrialization, a process, manifesting itself by increased fluctuations of crews in new employment places, i.e. one of employment mobility.6. The rate of growth of capital investments in the provinces shows a significant relationship with a quicker rate of housebreaking and a slower decrease in the number of clerical offences. An increase in the number of housebreaking is probably related to increased numbers of unskilled and ill-stabilized labour employed in capital investments.These are, in our opinion, the most important social and economic processes, differentiated as a result of an analysis of the material collected, whose relationships with the delinquency dynamics have already been discussed.First of all, most interesting is the fact that in the reporting provinces and periods of time such processes, as economic development, increased industrialization and increment of the urban population do not reveal any relationships with the delinquency dynamics.General views claiming close relations between,the processes mentioned and delinquency had somehow been shaken thereby. The final findings of our analysis have been confirmed by an undoubtful fact that in the reporting period in the province of Katowice, the most industrialized and urbanized province in Poland, there was the highest decrease in delinquency rates as compared with other provinces, and in 7964-1966, delinquency rates for the province of Katowice were much lower than the average rates for the country as a whole.It may then be assumed that there is no causation between such processes, as economic development, increased industrialization and increment of the urban population and the delinquency dynamics.Should in certain studies the two phenomena be found to appear, this would probably be due to other factors which failed to have been differentiated in the findings of such studies.Having considered the conclusions set forth in points 5 and 6, we believe that one of such factors is the social horizontal mobility which diminishes human environmental ties and limits possibilities for social control of individuals. Let us remember that point 5 was connected with a process characterized, among other things, by increased fluctuations of new plants' crews while point 6 - with a process of increased rates of capital construction where apparently, in that sort of work, poorly stabilized occupational categories are grouped. Simultaneously, both abovementioned processes reveal statistically significant connections with the delinquency dynamics.These remarks were confirmed by the conclusions drawn in the first part of this study, where it had been pointed out that increased rates and growth of delinquency in the regions under intensified industrialization programmes were related to sociodemographic processes characteristic for the social horizontal mobility. The sociodemographic processes, connected with an increased social horizontal mobility, consisting in migration and in frequent changes of employment by unskilled labour in general, are particularly intensified in an early phase of industrialization, i.e. in stages of construction, of new industrial objects and substantial auxiliary premise and of initial start of new industrial plants. But the later industrialization stages, where a phenomenon of a mass social advance of the population is observed, are not connected with increased delinquency rates.